Apakah Pengungkapan Corporate Social Responcibility (CSR) Mempengaruhi Return Saham? Analisis Reputasi Sebagai Pemediasi - Mulyani, Erly; Amar, Syamsul; Dwita, Vidyarini (Jurnal Ecogen, 2025)
With reputation serving as a mediator, this study seeks to ascertain the extent to which CSR disclosure affects stock return. This study employs a quantitative approach. focusing on noncyclical consumer companies listed on the IDX as the population.  The sampling technique used is purposive sampling. The results indictate that CSR influences the company’s reputation; however, CSR does not effect stock returns, and reputation cannot mediate the impact of CSR on stock returns.